The relationship between L2 motivation and transformative engagement in academic reading among EAP learners: Implications for reading self-regulation - Abdollahzadeh, Esmaeel; Amini Farsani, Mohammad; Zandi, Maryam (Frontiers in Psychology, 2022)
This study examined the relationship between L2 motivation and engagement in academic reading skill from the lenses of L2 motivational self-system (Dornyei, 2005) and Transformative Experience (Pugh, 2002). More specifically, following the transformative experience (TE) framework, we investigated the level of students’ engagement in reading skills inside and outside English classes. We also explored what motivational factors act as strong predictors of transformative experience, and whether L2 motivation and engagement of students differ across different disciplines. Stratified random sampling was followed to recruit 419 undergraduate EAP students studying in different majors. As such, we developed a questionnaire for measuring TE and utilized Taguchi et al. (2009) questionnaire to operationalize motivational self- system. We found that L2 motivation significantly co-varied with students’ level of engagement in English reading skill. Furthermore, the results of multiple regression analysis revealed that L2 learning experience and ideal L2 self were strong predictors of transformative engagement; ought-to L2 self played a marginal role in the occurrence of TE. Discipline-wise, Life Sciences students were considerably more motivated than those in Arts and Humanities. However, no significant difference was observed in the extent of transformative engagement among students across disciplinary groups. Implications for EAP instructors, educational authorities, and material and curricula developers are discussed.